Виявлення, аналіз і прогнозування параметрів ризику безвідмовного навантаження готової продукції на транспортно-логістичному терміналі підприємства - Аулін, В. В.; Кульова, Д. О.; Варваров, В. В.; Aulin V.; Kulova, D.; Varvarov, V. (ЦНТУ, 2025)
Стаття присвячена аналізу та оцінці ризиків безвідмовного навантаження готової продукції на постах навантаження транспортно-логістичного терміналу підприємства. Визначено закони розподілу щільності ймовірностей безвідмовної роботи буферних ємностей зони зберігання вантажів та величину ризику безвідмовного навантаження враховуючи тип продукції, фракційність, спосіб відвантаження. На основі проведеного ранжування величини ризику безвідмовного навантаження побудовано матрицю ризиків для всієї номенклатури готової продукції у розрізі відповідних зон зберігання та постів навантаження транспортно-логістичного терміналу підприємства. The study is focused on summarizing and analyzing the results obtained in the assessment of failure-free loading risks of finished products at the loading points of a transport and logistics terminal. The nomenclature of finished products and their corresponding storage zones was identified, considering the technological properties and specific characteristics of these cargoes to enhance the efficiency of terminal operations. The research established probability density distribution laws for the reliable operation of buffer storage tanks based on statistical analysis. A theoretical justification for failure-free loading risks and their components was developed using queuing theory. The main risks identified include the failure-free operation risk of buffer storage tanks, warehouse overflow due to the lack of storage space, vehicle downtime due to product unavailability, loading post system downtime due to the absence of a vehicle, and refusal to load due to full capacity at all terminal loading points etc.
Identification, Analysis, and Forecasting of Failure-Free Loading Risk Parameters for Finished Products at a Transport and Logistics Terminal
Keywords: транспортно-логістичний термінал; зона зберігання; пост навантаження; ризик; логістичний процес; готова продукція підприємства; transport and logistics terminal; storage zone; loading post; risk; logistics process; finished products of the enterprise